(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2015)
Background and objectives: Deaths resulting from hanging show features amongst which the ligature mark in the neck is considered to be decisive. The ligature mark is a pressure abrasion on the neck at the site of the ligature which appears as a groove. A sincere attempt is being made to study the correlation between the ligature mark and the material producing it along with the relation between external and internal features in the neck in cases of hanging. Methods: This prospective study was conducted among victims of hanging brought to Dr. B. R. Ambedkar Medical College morgue, Bangalore during the period November 2010−October 2012. Of all the cases brought to the department for medicolegal autopsy, cases in which death had resulted from hanging were identified. A sum total of 232 cases were selected for this prospective study. Detailed information regarding the deceased and the circumstances of death was collected from the police and relatives. Results: Dried salivary stains over the angle of mouth were observed in 65 cases. Knot was present on the right side of neck in 109 cases. Parchementisation was present in 156 cases. Peri ligature injuries in the form of rope burns, contusions and abrasions were seen in 33 cases. Involuntary discharge of faeces and semen was seen in 25 cases. Fracture of great cornu of hyoid bone was observed in 9 cases. Fracture of superior horn of thyroid cartilage was observed in 11 cases. Conclusion: Dried salivary stains over the angle of mouth were observed in one-fourth of the total cases studied. Knot was present on the right side of neck in half of cases. Parchementisation was present in many cases. Peri-ligature injuries were seen in 33 cases. Involuntary discharge of faeces and semen was seen in 25 cases. Fracture of great cornu of hyoid bone was observed in 9 cases. Fracture of superior horn of thyroid cartilage was observed in 11 cases.